Penerapan Model Pembelajaran Kooperatif Tipe Numbered Heads Together (NHT) Untuk Meningkatkan Hasil Belajar Ipa Biologi Peserta Didik Kelas X SMA Negeri Kecamatan Sulabesi Barat Kabupaten Kepulauan Sula - Najamudin Marsaoly (Peneliti.net, 2022)
This study aims to improve learning outcomes of Biology science learning for class X SMA Negeri Sula Besi Barat District, Sula Islands Regency through Numbered Heads Together (NHT) cooperative learning. The research method used is classroom action research (CAR) using a descriptive percentage approach. At the end of the individual test implementation cycle, to find out how far the students mastered the material in the second cycle. The researcher motivates students to be more serious in working on the questions, this is because the increase in the score of questions obtained in cycle I and cycle II contributes scores to their respective groups and determines the award that will be obtained at the end of the meeting. The research was carried out at SMA Negeri Sula Besi Barat District, Sula Islands Regency. The time of this research was carried out for one month starting from April 27 to May 27, 2020. The subjects of this research were students of class X SMA Negeri Sula Besi, West Regency. The variable in this study is student learning outcomes. The instrument used is a test to obtain data on student learning outcomes. The data analysis technique used in this research is descriptive percentage data analysis technique. The results showed that the presentation of student learning outcomes after learning using the NHT method in the first cycle was 61.25 and student learning outcomes increased in the second cycle to 86.25 from the data using the NHT learning method to improve student learning outcomes in class X State SMA, Sula District Besi Barat, Sula Islands Regency.